Β-elemene suppresses Warburg effect in NCI-H1650 non-small-cell lung cancer cells by regulating the miR-301a-3p/AMPKα axis. Issue 6 (18th June 2020) - Li, Lin; Zhao, Dongkai; Cheng, Guangyu; Li, Qingjie; Chu, Yunjie; Chu, Hongbo; Ding, Yunlu; Li, Chikun
Abstract: β-elemene has been evidenced to suppress the development of numerous cancers including lung cancer. Previous research has found that in A549 cells, β-elemene increased the expression of adenosine monophosphate-activated protein kinase (AMPK) α (AMPKα), which negatively regulates the Warburg effect. Bioinformatics predicted that binding sites exist between AMPKα and miR-301a-3p, an miRNA that has shown oncogenic function in many cancers. The aim of this work was to investigate the effect of β-elemene on the Warburg effect in non-small-cell lung cancer (NSCLC) cells and its mechanism. Herein, the expression of miR-301a-3p was evaluated in NSCLC cells. Then, miR-301a-3p was overexpressed or silenced by mimics or inhibitors, respectively, followed by treatment with AMPK agonists or antagonists. NSCLC cells subjected to miR-301a-3p overexpression or inhibition were further treated with β-elemene. The results demonstrated that AMPKα was targeted and negatively regulated by miR-301a-3p. AMPKα agonists attenuated the Warburg effect in NSCLC cells induced by miR-301a-3p, as evidenced by the decrease in glucose level, lactic acid level, and expression of metabolism-related enzymes (glucose transporter 1 (GLUT1), hexokinase 1 (HK1), and lactate dehydrogenase A (LDHA)). Additionally, β-elemene suppressed the expression of miR-301a-3p, enhanced that of AMPKα, and inhibited the Warburg effect in NSCLC cells. The results indicated that β-elemene attenuates the Warburg effect in NSCLC cells, possibly by mediating the miR-301a-3p/AMPKα axis.